Low incidence of atrial septal defects in nonmammalian vertebrates. Issue 3 (9th October 2019) - Jensen, Bjarke; Joyce, William; Gregorovicova, Martina; Sedmera, David; Wang, Tobias; Christoffels, Vincent M
Abstract: The atrial septum enables efficient oxygen transport by separating the systemic and pulmonary venous blood returning to the heart. Only in placental mammals will the atrial septum form by the coming‐together of the septum primum and the septum secundum . In up to one of four placental mammals, this complex morphogenesis is incomplete and yields patent foramen ovale. The incidence of incomplete atrial septum is unknown for groups with the septum primum only, such as birds and reptiles. We found a low incidence of incomplete atrial septum in 11 species of bird (0% of specimens) and 13 species of reptiles (3% of specimens). In reptiles, there was a trabecular interface between the atrial septum and the atrial epicardium which was without a clear boundary between left and right atrial cavities. In developing reptiles (four squamates and one crocodylian), the septum primum initiated as a sheet that acquired perforations and the trabecular interface developed late. We conclude that atrial septation from the septum primum only results in a low incidence of incompleteness. In reptiles, the atrial septum and atrial wall develop a trabecular interface, but previous studies on atrial hemodynamics suggest this interface has a very limited capacity for shunting. Abstract : The atrial septum (arrow) of the African helmeted turtle. There is a low incidence of atrial septal defects in nonmammalian vertebrates. Research Highlights: # We assessed the atrial septum in 11 species of birds and 13 species of reptiles. # Birds and reptiles appear to have a lower incidence of incomplete atrial septum than placental mammals